Estimation of left ventricular functions in patients with subclinical hypothyroidism: a meta-analysis - Li, Binyi; Huang, Yong; Li, Zheng (Frontiers in Endocrinology, 2023)
Objective: To evaluate left ventricular (LV) function in patients with subclinical hypothyroidism (ScH) compared to healthy individuals and to provide clinical hints for practitioners. Methods: PubMed, Embase, Cochrane Library, and Web of Science were systematically searched in this meta-analysis. Studies evaluating LV function in ScH patients were included. Standardized mean difference (SMD) and the 95% confidence intervals (CIs) were calculated as effect size. Heterogeneity and risks of bias of included studies were assessed. Results: A total of 9 studies were identified as eligible. The SMD for fractional shortening (FS, %) was -0.21 (95% CI: -0.60, 0.17; z = -1.08, p = 0.2788). The pooled SMD for systemic vascular resistance (SVR, dynes/sec•cm-5) was -0.41 (95% CI: -1.31, 0.49; z = -0.89, p = 0.3744). The pooled SMD for early diastolic mitral flow velocity/late diastolic mitral flow velocity (E/A) ratio was -0.74 (95% CI: -1.09, -0.39; z = -4.13, p < 0.001). The pooled SMD for ejection fraction (EF, %) was -0.35 (95% CI: --0.59, -0.12; z = -2.95, p = 0.0032). Conclusion: ScH patients had significantly worse LV function parameters than healthy controls. These changes in LV function may be involved in the management of ScH.